CHILDHOOD STROKES: EPIDEMIOLOGY, CLINICAL FEATURES AND RISK FACTORS - Bibi, Saima; Gilani, Syed Yasir H; Shah, Syed Raza Ali; Bibi, Sadia; Siddiqui, Tahir S. (Journal of Ayub Medical College Abbottabad, 2011)
Background: Stroke constitutes a significant health problem in paediatric population. The impact of childhood stroke can easily be realised in terms of economic, social and psychological burden related to disability of the affected children. The objective of study was to outline the epidemiology and clinical features of stroke in a cohort of Pakistani children and also ascertain the causes and potential risk factors in these patients. Methods: The study was conducted at the Department of Paediatrics, Ayub Teaching Hospital from January 2008 to October 2010. It was a cross sectional study. A total of 46 patients were included in the study who presented with cerebrovascular disease and were assessed clinically using general physical and systemic examination. The salient epidemiological, clinical, neuro-imaging and laboratory data was retrieved in designed protocol. Results: Out of a total of 46 patients, 50% were from either gender. Mean age of presentation was 39 months. Limb weakness was the commonest presenting feature being present in 37 (80.43%) patients. Infectious disorders was the most prevalent risk factor present in 31 (67.39%) patients followed by microcytic hypochromic anaemia in 28 (60.86%) patients. Conclusion: A Childhood stroke is a disorder with long term morbidity. Identification of risk factors is important in preventing the disorder by guiding appropriate interventions. Keywords: Childhood stroke, Infectious disorders, risk factors